Depressive symptoms in association with socio-demographic factors, family functioning and classroom enviroment among secondary school students in Samarahan - Azizah, Azhar (Universiti Malaysia Sarawak (UNIMAS), 2011)
Depression in adolescents has become one of the issues that spark concern among public health specialists and psychiatrists alike. The increasing trend worldwide and the destructive end results of adolescence depression need to be studied and analysed so that proper intervention can be institut~ The objectives of this cross sectional study were to detennine the prevalence of depressive symptoms among secondary school students in Samarahan area and to assess the factors that are significantly associated with depressive symptoms. Socio-demographic characteristics, perceived general family functioning and perceived school environment were the factors studied. The most common depressive symptoms were also being analysed in this study according to the Children Depressive Inventory (CDI) subscales. According to this study the rate of depressive' symptoms among secondary school students in Samarahan was quite high (34%). The ethnicity and school environment were .' significantly associated with depressive symptoms. HGwever gender, family functioning, type of schooling, staying with parents or single parent, number of siblings, birth order, family history of depression, staying with extended family member and area of residence have no significant association with depressive symptoms. Comparison of the median score of CD! showed that Chinese (21.32 ± 10.33) was more depressed compared to Malay (13.72 ± 6.87) and other Bumiputeras (12.71 ± 9.17). Furthermore the result also showed that students who stayed in rural area (13 ± 6.94) was less depressed compared to students stayed in urban area (14 ± 10.1). The most common depressive symptoms in this study were anhedonia (59%) and negative self-esteem (57%). In conclusion, the fmdings in this study highlight the importance of perceived school environment in relation with depressive symptoms which only recently taken into consideration in influencing teenagers psychological well being, particularly in Malaysia. Teachers, counsellors and other professionals who deal with adolescents, play an important role in linking the high risk adolescent to proper intervention strategies. Furthermore, one must not underestimate the influence of ethnicity in assessing the level of depressive symptoms among students.